Development Of Mini Generator Based On Wind Turbine Principle - Md. Rozali, Sahazati; Mohd Nor, Rozilawati; Abdul Rahim, Muhammad Atikkullah; Kamarudin, Muhammad Nizam; Hairi, Mohd Hendra (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
Shortage of resources to generate electricity is one of the big issues nowadays. Recently, in Malaysia, electricity is generated from fossil fuels and water flow pressure. However, fossil fuels are facing extinction problem due to the limited production of these sources while flow pressure water also has limitation to supply electrical energy to the residents. Besides, the usage of fossil as energy resources affect the environment. Thus, this research proposed a mini wind turbine as an alternative source to generate electricity for consumer daily usage. The designed generator is developed with a different number of blades and the operation is implemented by using Arduino. The analysis of the effectiveness of the designed system is measured through different evaluation of produced voltage based on a different number of fan blades and wind speed. The result shows that for ideal and simple wind turbine structure, the increment of rotational speed produced higher voltage and current. Thus, the system can be used as an alternative source of electrical generator for a small-scale individual user.